Youth and Drugs: Problems, Consequences and Preventives Measures - Ibrahim Umar Ibrahim (Archives of Current Research International, 2019)
Aim: This article reviews the effects and consequences of improper drugs use among youth. We tried to broaden our understanding on its effects, causes, and also to learn new preventive measures and principles that can be used to cure or mitigate the effects of such habits on people, and also to have comprehensive literature on the problem. Methodology: This paper focuses on the mains causes of the problems, i.e. drugs abused or substance abuse, among youth, its symptoms and sign, and consequences especially on health. And also preventives measures or principles that are prominent authors cited in their articles or reports which are believed to be effective.